Prispevek k poznavanju favne hroščev potapnikov Slovenije (Coleoptera: Hydraenidae, Hydrophilidae) - Drovenik, Božidar (Acta entomologica slovenica (Ljubljana), 2000)
Data on the distribution of 42 water-beetle species of the families Hydraenidae and Hydrophilidae are presented. 28 species were recorded in Slovenia for the first time.
Keywords: favna; Slovenia; Slovenija; vodni hrošči; zoologija; zoology